Mortality trends related to cardiogenic shock in heart failure patients aged 25 and older across the United States: A study utilizing the CDC WONDER database from 1999 to 2023 - Abdullah Naveed Muhammad; Sivaram Neppala; Himaja Dutt Chigurupati; Muhammad Omer Rehan; Hamza Naveed; Rabia Iqbal; Bazil Azeem; Ahila Ali; Mushood Ahmed; Prakash Upreti; Mobeen Zaka Haider; Yasar Sattar; et al. (International Journal of Cardiology: Heart & Vasculature, 2025)
Background: Cardiogenic shock (CS) remains crucial in mortality rates for heart failure (HF) patients. However, contemporary data on long-term mortality trends related to CS are limited. This study investigates demographic patterns and trends in CS mortality among HF patients over 25 years. Methods: Data from the Centers for Disease Control and Prevention’s Wide-ranging Online Data for Epidemiologic Research (CDC WONDER) database (1999–2023) included adults aged ≥25 diagnosed with HF and CS. Age-adjusted mortality rates (AAMRs) per 100,000 population and trends were analyzed using Joinpoint regression to find the average annual percent change (AAPC) and annual percent change (APC). Results: Between 1999 and 2023, there were 108,514 deaths linked to cardiogenic shock among heart failure patients, with AAMRs increasing from 1.2 to 4.6 per 100,000 (AAPC: 5.90). The most significant increases occurred from 2009 to 2021 (APC: 14.17), followed by a sustained rise from 2021 to 2023 (APC: 7.83). Men consistently exhibited higher AAMRs than women (2.4 vs. 1.3), and Black individuals had the highest mortality rates across all racial and ethnic groups. Furthermore, mortality rates were notably higher in rural areas compared to urban settings (1.7 vs. 1.5). Conclusion: In the past 25 years, CS-related mortality in HF patients has increased nearly fourfold. This trend highlights the need to investigate its causes, including potential deteriorating health outcomes or improved healthcare access. Special focus should be on high-risk groups like men, Black individuals, and rural residents, as targeted interventions could mitigate disparities and enhance outcomes.